Lymph node metastasis of primary endometrial cancers: Associated proteins revealed by MALDI imaging. Issue 11 (10th May 2016) - Mittal, Parul; Klingler‐Hoffmann, Manuela; Arentz, Georgia; Winderbaum, Lyron; Lokman, Noor A; Zhang, Chao; Anderson, Lyndal; Scurry, James; Leung, Yee; Stewart, Colin JR; Carter, Jonathan; Kaur, Gurjeet; et al.
Abstract : Metastasis is a crucial step of malignant progression and is the primary cause of death from endometrial cancer. However, clinicians presently face the challenge that conventional surgical‐pathological variables, such as tumour size, depth of myometrial invasion, histological grade, lymphovascular space invasion or radiological imaging are unable to predict with accuracy if the primary tumour has metastasized. In the current retrospective study, we have used primary tumour samples of endometrial cancer patients diagnosed with ( n = 16) and without ( n = 27) lymph node metastasis to identify potential discriminators. Using peptide matrix assisted laser desorption/ionisation mass spectrometry imaging (MALDI‐MSI), we have identified m/z values which can classify 88% of all tumours correctly. The top discriminative m/z values were identified using a combination of in situ sequencing and LC‐MS/MS from digested tumour samples. Two of the proteins identified, plectin and α‐Actin‐2, were used for validation studies using LC‐MS/MS data independent analysis (DIA) and immunohistochemistry. In summary, MALDI‐MSI has the potential to identify discriminators of metastasis using primary tumour samples.